The daughter-in-law - Diamond, Diana (New York : St. Martin's Press, 2003)
When a reformed wealthy playboy dies in a scuba diving accident, the victim's mother works to prove that his new wife, who was responsible for his mended ways, is behind his death.
Keywords: Accident victims -- Family relationships -- Fiction; Daughters-in-law -- Fiction; Mothers-in-law -- Fiction; Rich people -- Fiction; Widows -- Fiction